Patterns of constitutional design : the role of citizens and elites in constitution-making - Wheatley, Jonathan, 1964-; Mendez, Fernando, 1972- (Ashgate, 2013)
Bridging the gap between law and political science this book draws together divergent research on the role of constitution making in conflict resolution, constitutional law and democratization and employs a wide variety of qualitative and quantitative methods to unfold and explore the political frameworks of the states affected. Comparative analysis is used to investigate potential causal chains between constitution-making processes and their outcomes in terms of stability, conflict resolution and democracy. By focusing on both procedure and context, the book explores the impact of constitutio.